Myth, Form and Intertextuality in Edwin Muir - Insausti, Gabriel (International Journal of English Studies, 2021)
Edwin Muir has often embarrassed critics as a rara avis. He was overlooked by anthologists before 1950 and, although subsequent anthologies never failed to include him, he was still hard to place for many readers. Labelled as a “traditionalist” or a “craftsman”, his later work proves however that Muir was much more. Understanding his use of myth, form and intertextuality enables us to rethink the significance of his work in the twentieth-century context.